Characterization of voiding function and structural bladder changes in a rat model of neurogenic underactive bladder disease. Issue 5 (7th February 2018) - Weyne, Emmanuel; Dewulf, Karel; Deruyer, Yves; Rietjens, Roma; Everaerts, Wouter; Bivalacqua, Trinity J.; De Ridder, Dirk; Van der Aa, Frank; Albersen, Maarten
Abstract : Objectives: To create an animal model for neurogenic underactive bladder disease (UAB) and identify markers to describe secondary myogenic changes in the bladder wall. Materials and Methods: Male rats underwent either bilateral pelvic nerve injury or sham surgery. Four weeks after surgery functional evaluation was performed and tissue was harvested. Functional evaluation consisted of analysis of voiding pattern, 24‐h urine collection in a metabolic cage, in vivo cystometry and in‐vitro contractile function assessment. PCR and immunohistochemical localization of different smooth muscle cell and extracellular matrix markers was performed on bladder strips. Results: After pelvic nerve injury, dry bladder weight increased and voiding contractions were absent, resulting in overflow incontinence. In‐vitro contractile response to carbachol was decreased. This was paired with an upregulation of synthetic smooth muscle cell (SMC) markers mRNA expression such as retinol binding protein 1 (RBP1), myosin 10 (MYH10) and osteopontin (OPN), and a downregulation of contractile SMC marker smoothelin (SMTL). The SMTL/OPN mRNA ratio was 50 times higher in sham bladders compared to PNI bladders. Conclusions: The loss of in‐vivo and in‐vitro contractile function following pelvic nerve transection is characterized by a switch from a contractile to synthetic SMC phenotype, which is best characterized by the ratio SMTL/OPN mRNA expression. Modulating this phenotypical switch is a potential target for the development of UAB therapy. We suggest for the first time a set of markers that may be useful to evaluate therapeutic strategies on improvements in bladder wall structure.